Increasing Public Speaking and Self-Confidence through The Muhadharah Method - Muslim, Khidayat; Anjani, Mutiara; Aziz, Nur; Hidayat, Yayat (Bestari, 2023)
Enhancing one's public speaking abilities and self-assurance is a vital element in the personal growth of individuals, particularly in the pesantren setting, which greatly influences character development. The objective of this study is to investigate the efficacy of the Muhadharah method in improving public speaking abilities and self-assurance among students at Pesantren Nurul Huda Cikandri. The research methodology utilizes a qualitative approach, with a case study serving as the primary design. Data is collected through the use of participatory observation, in-depth interviews, and comparisons specifically pertaining to the Muhadharah technique. The findings suggest that the Muhadharah approach plays a vital role in enhancing students' public speaking skills and self-assurance. Pesantren Nurul Huda Cikandri employs the Muhadharah technique by utilizing a participatory and immersive approach. Students participate in public speaking events under the leadership and mentorship of experienced individuals. The data indicates a notable improvement in the students' speaking abilities, understanding of the subject matter, and level of self-assurance. This study enhances our comprehension of the efficacy of the Muhadharah approach within the realm of pesantren education. The findings of this research can provide a basis for the creation of educational programs aimed at enhancing public speaking skills and self-assurance, not just in pesantren but also in other educational establishments.